Anonymous

# √3+√27 How to do Step please Thx?

Update:

Simplify it

### 15 Answers

Relevance

- la consoleLv 75 months ago
= √3 + √27

= √3 + √(9 * 3)

= √3 + (√9 * √3)

= √3 + (√3² * √3)

= √3 + (3 * √3)

= √3 + 3√3

= 4√3

- What do you think of the answers? You can sign in to give your opinion on the answer.
- llafferLv 75 months ago
√3 + √27

Simplify the square root of 27, knowing that you can factor a 9 out of it which is a perfect square to get:

√3 + √(9 * 3)

√3 + 3√3

Now you can combine like terms to get:

4√3

- DavidLv 75 months ago
It is the same as (1 times square root of 3 )+ (3 times the square root of 3) = 4 times square root of 3

The simplest way is to use your calculator.

- TomVLv 75 months ago
How to do what? What do you want done with the expression?

The expression can be written in a simpler form if you recognize that √3 is a factor of both terms.

√3 + √(3*9)

= √3 + 3√3

= 4√3

Still have questions? Get answers by asking now.

Because √3 + 3√3 = (1)√3 + (3)√3 = (1+3)√3 = 4√3